Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1017/jfm.2013.181
|View full text |Cite
|
Sign up to set email alerts
|

Physical processes influencing acoustic radiation from jet engine inlets

Abstract: Numerical simulations of acoustic radiation from a jet engine inlet are performed using advanced computational aeroacoustics algorithms and high-quality numerical boundary treatments. As a model of modern commercial jet engine inlets, the inlet geometry of the NASA Source Diagnostic Test is used. Fan noise consists of tones and broadband sound. This investigation considers the radiation of tones associated with upstream-propagating duct modes. The primary objective is to identify the dominant physical processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…Tam et al 98 shed light on the physical processes that control noise radiation from engine inlets. Two important effects of diffraction and refraction on inlet fan tones were identified and explained.…”
Section: Computational Aeroacoustics Applicationsmentioning
confidence: 99%
“…Tam et al 98 shed light on the physical processes that control noise radiation from engine inlets. Two important effects of diffraction and refraction on inlet fan tones were identified and explained.…”
Section: Computational Aeroacoustics Applicationsmentioning
confidence: 99%
“…In the lateral direction the 10 angle of attack case shows a strong tendency to radiate to one side (Figure 12, front and top view) with highly distorted waves leaving the nacelle. As discussed by Tam et al 17 , a major impact on the directivity for a given frequency and mode are diffraction and refraction effects caused by the mean flow orientation (stagnation points and overspeed regions). Tam et al 17 had investigated these effects separately and for a symmetric inlet contour.…”
Section: Free-field Radiationmentioning
confidence: 99%
“…As discussed by Tam et al 17 , a major impact on the directivity for a given frequency and mode are diffraction and refraction effects caused by the mean flow orientation (stagnation points and overspeed regions). Tam et al 17 had investigated these effects separately and for a symmetric inlet contour. Here, the sound field is composed of a large number of circumferential modes (see Figure 9) and the mean flow is non-uniform, resulting in a more complicated directivity pattern.…”
Section: Free-field Radiationmentioning
confidence: 99%
“…The phenomenon of acoustic waves propagating in complex flows such as shear layers or a vortex often exists in aerospace engineering [ 1 , 2 , 3 , 4 ]. Studies have shown that such flow structures will change the characteristics of acoustic wave propagation, leading to refraction, reflection, and scattering and thus affect the measurement and localization of sound source [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%